Race, sex, social class: the influence of stress responsiveness on well-being among American families - White, Vera A (Kansas State University, 2007)
The purpose of this study was to explore the relationship between chronic stressors-believed to be a condition present by race, sex, and social class and Well-being when mediated by individual resources and perceptions. Additionally, this study examined the utility of the proposed ABC-WB Model of Well-Being adapted from the ABC-X Model. The data used in this dissertation were gleaned from the 2004 General Social Survey which contained a weighted sample of 3,260 respondents. Several observed indicators were used to define each of the latent constructs corresponding to theoretical variables of the ABC-WB model. Each of these constructs contributed to the overall model in some way despite some inconsistent findings. The utility of the model was examined with multiple indicators for Stressor. None of the four research hypotheses were supported by the tested models. The data models were then respecified. This process did not produce any working structural models as well. Nevertheless, the findings revealed that well-being was an important factor to consider in the ABC-WB model. Despite the shortcomings of the model the stressor measurement revealed a direct but mild relationship with well-being. In all the models, Stressor was tempered by Resources and Perceptions both of which had a strong relationship with well-being. The selected models suggested that despite the lack of fit, largely to do with data restrictions rather than model specificity, the overall ABC-WB model has research potential.
Keywords: Stressor; Well-Being; ABC-X; Life Satisfaction; Sociology, Individual and Family Studies (0628)